Die Magische Dose : Documenta 9. - Hoet, Jan; Heinz, Marianne; Arends, Toos; Ketelsen, Thomas; Documenta 9, Kassel, 1992 (Stuttgart : Edition Cantz, 1992)
Baikas, Nicos ; Caldas, Waltercio ; Saint Clair Cemin ; Dimitrijevic, Braco ; Fabre, Jan ; Fortuyn/O'Brien ; Funakoshi, Katsura ; Grauerholz, Angela ; Hopkins, Peter ; Katase, Kazuo ; Kosuth, Joseph ; Leonard, Zoe ; Merz, Gerhard ; Prina, Stephen ; Rantzer, Philip ; Steinbach, Haim ; Takeoka, Yuji ; Zobernig, Heimo
Documenta 9, Staatliche Museen Kassel - Neue Galerie, Kassel, 13 juni tot 20 september 1992
boek